A multicentre randomised study of intrasphincteric botulinum toxin in patients with oesophageal achalasia. Issue 5 (1st May 2000) - Annese, V; Bassotti, G; Coccia, G; Dinelli, M; D'Onofrio, V; Gatto, G; Leandro, G; Repici, A; Testoni, P A; Andriulli, A; ,
Abstract : BACKGROUND: Intrasphincteric injection of botulinum toxin (Botx) has been proposed as treatment for oesophageal achalasia. However, the predictors of response and optimal dose remain unclear. AIMS: To compare the effect of different doses of Botx and to identify predictors of response. PATIENTS/METHODS: A total of 118 achalasic patients were randomised to receive one of three doses of Botx in a single injection: 50 U (n=40), 100 U (n=38), and 200 U (n=40). Of those who received 100 U, responsive patients were reinjected with an identical dose after 30 days. Clinical and manometric assessments were performed at baseline, 30 days after the initial injection of botulinum toxin, and at the end of follow up (mean 12 months; range 7–24 months). RESULTS: Thirty days after the initial injection, 82% of patients were considered responders without a clear dose related effect. At the end of follow up however, relapse of symptoms was evident in 19% of patients who received two injections of 100 U compared with 47% and 43% in the 50 U and 200 U groups, respectively. Using Kaplan-Meier analysis, patients in the 100×2 U group were more likely to remain in remission at any time (p<0.04), with 68% (95% CI 59–83) still in remission at 24 months. In a multiple adjusted model, response to Botx was independently predicted by the occurrence of vigorous achalasia (odds ratio 3.3) and the 100×2 U regimen (odds ratio 3.2). CONCLUSIONS: Two injections of 100 U of Botx 30 days apart appeared to be the most effective therapeutic schedule. The presence of vigorous achalasia was the principal determinant of the response to Botx.